Employment and disability among young Australians and associations with psychological distress during the COVID-19 pandemic - Marissa Shields; Matthew J. Spittal; Stefanie Dimov; Anne Kavanagh; Tania L. King (Elsevier, 2022)
Background: Emerging global data indicates that the employment status and mental health of young people is being adversely impacted by the COVID-19 pandemic. However, little research has focused on young people with disabilities, despite their lower pre-pandemic employment rates and poorer mental health. We quantified the association between employment status and mental health among young Australians, and tested for effect modification by disability status. Methods: Linear regression analysis of Wave 9 (October-December 2020) of the Longitudinal Study of Australian Children (LSAC) assessing the association between employment status (employed, unemployed) on psychological distress (Kessler-10) and including an interaction term for employment status and disability. Results: The association between employment status and psychological distress differed by disability status. Young adults with disabilities had higher adjusted mean K10 scores indicating greater psychological distress both when they were employed (mean 22.99, 95% CI 21.41, 24.58) and unemployed (mean 29.19, 95% CI 25.36, 33.03) compared to their peers without disabilities (employed mean 18.72, 95% CI 17.75, 19.70; unemployed mean 20.45, 95% CI 18.60, 22.29). Conclusion: Young Australians in general may benefit from additional supports to improve their employment and mental health outcomes. Young people with disabilities may particularly benefit from targeted supports to gain and maintain employment and improve mental health.